Diversity, ecology and habitat suitability of Gigantochloa in Central Sumatra - Syauqi, M Farid; Chikmawati, Tatik; Fitmawati; Ariyanti, Nunik Sri (Agriculture and Natural Resources, 2023)
Importance of the work: Sumatra Island, with 76 species of bamboo, is the center of bamboo biodiversity in Indonesia. Objectives: Gigantochloa species diversity was investigated and environmental factors analyzed to create prediction maps of species distribution and habitat suitability. Materials & Methods: The Gigantochloa samples were collected from various habitats in Central Sumatra. The horizontal distribution was mapped using the QGIS 3.20.2 software, while the vertical distribution was analyzed using the Past 4.03 software. Correlations between species and environmental factors were subjected to canonical correspondence analysis using the CANOCO 4.5 software and habitat suitability was analyzed using the MaxEnt package. Results: Fourteen species of Gigantochloa were identified from Central Sumatra, one of which was G. kuring, which is endemic to Sumatra. Gigantochloa was distributed from the lowlands up to 1,367 m above sea level. The distribution of Gigantochloa was influenced mostly by soil pH, soil moisture, wind and light. Analysis using MaxEnt indicated habitat that was suitable for Gigantochloa in Central Sumatra, with an area under the curve value of 0.851. Mapping showed Central Sumatra had suitability levels of high (5.9%), moderate (8.1%), low (21.7) and unsuitable (64.7%). The endemic G. kuring had the highest habitat suitability in Jambi province. Main Finding: The collected information could be used to determine the best locality for further investigation regarding the diversity and taxonomy of Gigantochloa and as basic data to determine appropriate strategies to protect Gigantochloa habitats, especially for endemic species.